Long-term effects of sulphide on the enhanced biological removal of phosphorus: The symbiotic role of Thiothrix caldifontis. (1st June 2017) - Rubio-Rincón, F.J.; Welles, L.; Lopez-Vazquez, C.M.; Nierychlo, M.; Abbas, B.; Geleijnse, M.; Nielsen, P.H.; van Loosdrecht, M.C.M.; Brdjanovic, D.
Abstract: Thiothrix caldifontis was the dominant microorganism (with an estimated bio-volume of 65 ± 3%) in a lab-scale enhanced biological phosphorus removal (EBPR) system containing 100 mg of sulphide per litre in the influent. After a gradual exposure to the presence of sulphide, the EBPR system initially dominated by Candidatus Accumulibacter phosphatis Clade I (98 ± 3% bio-volume) (a known polyphosphate accumulating organism, PAO) became enriched with T. caldifontis . Throughout the different operating conditions studied, practically 100% phosphate removal was always achieved. The gradual increase of the sulphide content in the medium (added to the anaerobic stage of the alternating anaerobic-aerobic sequencing batch reactor) and the adjustment of the aerobic hydraulic retention time played a major role in the enrichment of T. caldifontis . T. caldifontis exhibited a mixotrophic metabolism by storing carbon anaerobically as poly-β-hydroxy-alkanoates (PHA) and generating the required energy through the hydrolysis of polyphosphate. PHA was used in the aerobic period as carbon and energy source for growth, polyphosphate, and glycogen formation. Apparently, extra energy was obtained by the initial accumulation of sulphide as an intracellular sulphur, followed by its gradual oxidation to sulphate. The culture enriched with T. caldifontis was able to store approximately 100 mg P/g VSS. This research suggests that T. caldifontis could behave like PAO with a mixotrophic metabolism for phosphorus removal using an intracellular sulphur pool as energy source. These findings can be of major interest for the biological removal of phosphorus from wastewaters with low organic carbon concentrations containing reduced S-compounds like those (pre-)treated in anaerobic systems or from anaerobic sewers. Graphical abstract: Highlights: Satisfactory EBPR was achieved with up to 100 mg H2 S-S/L present in the influent. Thiothrix caldifontis played a major role through mixotrophic growth in the EBPR process. Thiothrix caldifontis stored acetate as PHA under anaerobic conditions. The enriched Thiothrix caldifontis culture stored up to 100 mg P/gVSS under aerobic conditions. The oxidation of Poly-sulphur appeared to provide the required energy for polyphosphate formation under aerobic conditions.